Epidemiological review of confirmed Lassa fever cases during 2016-2018, in Plateau State, North Central Nigeria. - Simji Gomerep; Martina Nuwan; Solomon Butswat; Joyce Bartekwa; Solomon Thliza; Christian Akude; Ayanfe Omololu; David Shwe; Rachel Reyna; Tomoko Makishima; Slobodan Paessler; Nathan Shehu (PLOS Global Public Health)
Lassa fever (LF) is endemic in West Africa and constitutes a significant public health concern due to its potential for epidemics and associated high mortality. The first reported case and management of Lassa fever in Plateau State occurred more than 50 years ago. We set out to undertake a three-year epidemiological review of LF cases in Plateau State, North Central Nigeria. This is a retrospective study of all confirmed LF cases in Plateau State between 2016 and 2018. Plateau state Lassa fever- Line list and patient case records were used to extract relevant data. Lassa PCR was carried out at the NCDC accredited Laboratory network. Data analysis was done using STATA version SE14.1. Forty-four persons (44) had confirmed LF over the examined period, 18 (41%) in 2016, 15 (34%) in 2017 and 11 (25%) in 2018. The mean age was 29.7±14.6 years and 53% were males. Sixty-six percent (66%) of the patients resided in rural areas. It affected all local government areas (LGA) in the state except Pankshin, Jos East and Kanke LGAs. Twenty-five percent (25%) of the cases occurred among underprivileged communities of Jos North and another 25% in rural dwellers of Langtang North. Fifty-nine percent (59%) of cases occurred during the 1st quarter, 27% the 2nd quarter and 18% the 3rd quarter of the year. The case fatality rate was 57%. LF is endemic in Plateau State. Prevention strategies must be sustained year round and target the youth, urban and rural underprivileged communities. There is also need for case management improvement to reduce mortality.